Adaptations to endosymbiosis in a cnidarian-dinoflagellate association: differential gene expression and specific gene duplications. - Philippe Ganot; Aurélie Moya; Virginie Magnone; Denis Allemand; Paola Furla; Cécile Sabourault (PLoS Genetics, 2011)
Trophic endosymbiosis between anthozoans and photosynthetic dinoflagellates forms the key foundation of reef ecosystems. Dysfunction and collapse of symbiosis lead to bleaching (symbiont expulsion), which is responsible for the severe worldwide decline of coral reefs. Molecular signals are central to the stability of this partnership and are therefore closely related to coral health. To decipher inter-partner signaling, we developed genomic resources (cDNA library and microarrays) from the symbiotic sea anemone Anemonia viridis. Here we describe differential expression between symbiotic (also called zooxanthellate anemones) or aposymbiotic (also called bleached) A. viridis specimens, using microarray hybridizations and qPCR experiments. We mapped, for the first time, transcript abundance separately in the epidermal cell layer and the gastrodermal cells that host photosynthetic symbionts. Transcriptomic profiles showed large inter-individual variability, indicating that aposymbiosis could be induced by different pathways. We defined a restricted subset of 39 common genes that are characteristic of the symbiotic or aposymbiotic states. We demonstrated that transcription of many genes belonging to this set is specifically enhanced in the symbiotic cells (gastroderm). A model is proposed where the aposymbiotic and therefore heterotrophic state triggers vesicular trafficking, whereas the symbiotic and therefore autotrophic state favors metabolic exchanges between host and symbiont. Several genetic pathways were investigated in more detail: i) a key vitamin K-dependant process involved in the dinoflagellate-cnidarian recognition; ii) two cnidarian tissue-specific carbonic anhydrases involved in the carbon transfer from the environment to the intracellular symbionts; iii) host collagen synthesis, mostly supported by the symbiotic tissue. Further, we identified specific gene duplications and showed that the cnidarian-specific isoform was also up-regulated both in the symbiotic state and in the gastroderm. Our results thus offer new insight into the inter-partner signaling required for the physiological mechanisms of the symbiosis that is crucial for coral health.